2016
DOI: 10.1186/s12934-016-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

GqqA, a novel protein in Komagataeibacter europaeus involved in bacterial quorum quenching and cellulose formation

Abstract: BackgroundWe report on the functional screening and identification of an active quorum quenching (QQ) gene in the Komagataeibacter europaeus strain CECT 8546, which is a member of the acetic acid bacteria (AAB).ResultsUsing a previously published screening protocol (Schipper et al., in Appl Environ Microbiol 75:224–233, 2009. doi: 10.1128/AEM.01389-08) for QQ genes, we identified a single gene, designated gqqA, that interfered strongly with bacterial quorum sensing (QS) in various reporter strains. It encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…16 A recent study showed that gqqA encoded a novel protein involving in bacterial quorum quenching and cellulose formation, indicating more attention should be paid to BC synthesis mechanisms in bacteria. 17 Since BC production is naturally occurring, most BCproducing bacteria are oen isolated from the carbohydratecontaining substances such as rotten fruits, kombucha and vinegar. 16,18,19 In the present study, a bacterium belonging to the genus Komagataeibater was rstly isolated from a famous vinegar factory located in Yongchun, Quanzhou, China.…”
Section: Introductionmentioning
confidence: 99%
“…16 A recent study showed that gqqA encoded a novel protein involving in bacterial quorum quenching and cellulose formation, indicating more attention should be paid to BC synthesis mechanisms in bacteria. 17 Since BC production is naturally occurring, most BCproducing bacteria are oen isolated from the carbohydratecontaining substances such as rotten fruits, kombucha and vinegar. 16,18,19 In the present study, a bacterium belonging to the genus Komagataeibater was rstly isolated from a famous vinegar factory located in Yongchun, Quanzhou, China.…”
Section: Introductionmentioning
confidence: 99%
“…The method used was described previously, with some modifications ( Ishida et al, 1998 ; Tang et al, 2015 ; Valera et al, 2016 ). Briefly, P. aeruginosa PAO1, which was grown overnight in LB, was diluted to 10 6 CFU/ml in a 12-well cell culture plate with different concentrations of sterile Aii810 (0.05, 0.5, or 5 U/ml).…”
Section: Methodsmentioning
confidence: 99%
“…AHL-lactonases degrade AHLs by breaking the lactone bond ( Dong et al, 2000 ); AHL-acylases hydrolyze AHLs by degrading the amide linkage and separating the AHL into homoserine lactone and fatty acid ( Lin et al, 2003 ); AHL-oxidases degrade signal molecules by oxidizing the u-1, u-2, and u-3 carbons of the acyl chain of AHL ( Chowdhary et al, 2007 ). Furthermore, some enzymes have shown anti-QS activity against P. aeruginosa infection ( Bijtenhoorn et al, 2011a ; Migiyama et al, 2013 ; Tang et al, 2015 ; Valera et al, 2016 ). Very few reports are available on lactonases with novel characteristics, such as cold adaptation and high hydrolytic activity, because such enzymes are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel cellulose biosynthesis regulator, the quorum‐quenching protein GqqA, has been described. The addition of recombinant GqqA protein to growing cultures of the Komagataeibacter europaeus CECT8546 exerted a strong impact on cellulose production (Valera et al ., ). The density of the culture increased overtime in the presence of the GqqA protein, whereas the control cultures did not display any altered behaviour.…”
Section: Regulation Of the Biosynthesis Of Bncmentioning
confidence: 97%
“…(Valera et al . () suggested that this effect is attributable to alterations in the produced AHL molecules.…”
Section: Regulation Of the Biosynthesis Of Bncmentioning
confidence: 99%